COPI budding within the Golgi stack - Popoff, Vincent; Adolf, Frank; Brügger, Britta; Wieland, Felix T. (Cold Spring Harbor perspectives in biology, 2011)
The Golgi serves as a hub for intracellular membrane traffic in the eukaryotic cell. Transport within the early secretory pathway, that is within the Golgi and from the Golgi to the endoplasmic reticulum, is mediated by COPI-coated vesicles. The COPI coat shares structural features with the clathrin coat, but differs in the mechanisms of cargo sorting and vesicle formation. The small GTPase Arf1 initiates coating on activation and recruits en bloc the stable heptameric protein complex coatomer that resembles the inner and the outer shells of clathrin-coated vesicles. Different binding sites exist in coatomer for membrane machinery and for the sorting of various classes of cargo proteins. During the budding of a COPI vesicle, lipids are sorted to give a liquid-disordered phase composition. For the release of a COPI-coated vesicle, coatomer and Arf cooperate to mediate membrane separation.
Gesehen am 10.01.2023